a n − 1 n ! = a n
Consider a recurrence relation above for n = 1 , 2 , 3 , … and a 0 = 1 . If the value of the series n = 0 ∑ ∞ a 2 n 1 can be expressed as e α / β , where α and β are coprime positive integers , find α + β .
Clarification : e ≈ 2 . 7 1 8 2 8 denotes the Euler's number .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Taylor Series - Problem Solving
By the reccurence we have a 1 = 1 a 2 = 2 a 3 = 3 a 4 = 2 ⋅ 4 a 5 = 1 ⋅ 3 ⋅ 5 a 6 = 2 ⋅ 4 ⋅ 6 so a 2 n = 2 ⋅ 4 ⋅ 6 ⋯ 2 n a 2 n = 2 n n ! hence n = 0 ∑ ∞ a 2 n 1 = n = 0 ∑ ∞ n ! ( 2 1 ) n = e 1 / 2 α + β = 3
First few a n indicates that a n = n ! ! . Let us prove it by induction that the claim that a n = n ! ! applies to all n ≥ 0 .
For n = 0 , a 0 = 0 ! ! = 1 as given, therefore, the claim is true for n = 0 .
Assuming that the claim is true for n , then we have a n + 1 = a n ( n + 1 ) ! = n ! ! ( n + 1 ) ! = ( n + 1 ) ! ! . The claim is also true for n + 1 , therefore, it is true for all n ≥ 0 .
Now, we have: n = 0 ∑ ∞ a 2 n 1 = n = 0 ∑ ∞ ( 2 n ) ! ! 1 = n = 0 ∑ ∞ 2 n n ! 1 = e 2 1
⟹ α + β = 1 + 2 = 3
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Taylor Series - Problem Solving
a n = ( n − 1 ) ! n ! × a n − 1
= ( n − 1 ) ! n ! × a n − 2 ( n − 2 ) !
= ( n − 1 ) ! n ! × ( n − 3 ) ! ( n − 2 ) ! × a n − 3
⋯ ⋯
⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ = ( n − 1 ) ! n ! × ( n − 3 ) ! ( n − 2 ) ! ⋯ × 2 if n is even = ( n − 1 ) ! n ! × ( n − 3 ) ! ( n − 2 ) ! ⋯ × 3 × 1 if n is odd
Hence if n is even,
a n = n × ( n − 2 ) × ( n − 4 ) × 2
= 2 n / 2 × ( 2 n ) !
Required sum is therefore:
∴ n = 0 ∑ ∞ 2 n × n ! 1 = n = 0 ∑ ∞ n ! ( 2 1 ) n = e 1 / 2
Hence, 1 + 2 = 3
Alternate Solution:- Above was the actual proof but after writing few terms one can resort to induction to prove:
a 2 n = 2 n n ! , n ∈ N This is obviously true for n = 1 since a 2 = 2 . Now assuming it to be true for some natural k i.e a 2 k = 2 k k ! , we have to prove it also holds for k + 1 .
Using given recurrence relation , a 2 k + 2 = ( 2 k + 2 ) × a 2 k ( 2 k ) ! = 2 k + 1 ( k + 1 ) !
Hence whenever statement is true for some natural k it is also valid for k + 1 . Hence by induction the statement is true for all natural numbers i.e
a 2 n = 2 n n ! ∀ n ∈ N
And the rest process is same as above.